PENERAPAN SISTEM PERTANIAN ORGANIK PADA KOMODITAS DALAM MENGHADAPI LAHAN KRITIS DI KELOMPOK TANI SUMBER MAKMUR ABADI PASURUAN JAWA TIMUR - Haidar Fari Aditya; Fitri Wijayanti; Ramadhani Mahendra Kusuma; Safira Rizka Lestari; Puji Lestari Tarigan; Wiga Fikri Destianisma; Yudi Nur Supriadi (Gapenas Publisher, 2023)
From the conservation standpoint, critical land is land that can no longer function to operate the water system, soil resources, and biodiversity that lives on the land. Critical land exhibits signs indications of environmental degradation as a result of numerous sorts of improper land resource utilization. The impact of critical land results in a decrease in the function of conservation, production function, and socio-economic life of the community. The Sumadi Farmer Group encountered hurdles downstream (marketing) and upstream (cultivation) due to limited land use and lack of human resources who understood plant conservation systems. Therefore, this community service aims to preserve critical land with biological conservation methods by improving soil quality, cultivating healthy plants, and controlling pests and diseases using vegetable pesticides. The activity began with the observation of agroforestry planting land, then socialization and presentation of material by the team of lecturers, followed by demonstrations on the land, and ended with an evaluation. Empowered with an understanding of cultivation techniques and restorative plant care, the Sumadi farmer group is passionate about developing an organic farming system to overcome land issues